The Role of Art Education in Developing Creativity and Expression in Early Childhood - Nandi Saefurrohman (Journal of Pedagogi, 2024)
The purpose of this article is to explore the role of art education in developing creativity and emotional expression in early childhood. This research uses a qualitative approach. The research design is a case study, which allows for in-depth analysis of the phenomenon of art education in early childhood education environments. The participants in this study are teachers and caregivers who teach art in the school. The expected total number of participants is 50 teachers. The data collection techniques used include observation, in-depth interviews, and document analysis. The results of the study show that art education significantly enhances children's ability to generate new ideas, take creative risks, and solve problems in innovative ways. Art activities have also been proven to help children express emotions and enhance emotional well-being. In addition, art education contributes to understanding basic concepts in academic subjects and the development of fine and gross motor skills. The implications of this research indicate that art education is a key element in supporting the holistic development of early childhood. Therefore, it is important for educators, parents, and communities to integrate art into children's daily lives..